2018
DOI: 10.1007/s00423-018-1651-8
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted Roux-en-Y hepaticojejunostomy after bile duct injury

Abstract: Robotic surgery is feasible and can be safely performed, with acceptable short-term results, in bile duct injury repair providing the advantages of minimally invasive surgery. Further studies with larger number of cases and longer follow-up are needed to establish the role of robotic assisted approaches in the reconstruction of BDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 27 publications
0
6
0
3
Order By: Relevance
“…In 1893, César Roux designed a Roux-en-Y jejunal loop for gastrojejunostomy, later used in CJS to prevent intestinal fluid reflux (15). At present, Roux-en-Y CJS is the most commonly used method for bile duct reconstruction in the clinical setting (16,17). However, regardless of the type of CJS, because of the deprecation of the sphincter of Oddi, the problem of intestinal fluid reflux cannot be solved completely, and repeated cholangitis stimulation will cause scar tissue hyperplasia and eventually lead to anastomotic stricture, and even cancer (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…In 1893, César Roux designed a Roux-en-Y jejunal loop for gastrojejunostomy, later used in CJS to prevent intestinal fluid reflux (15). At present, Roux-en-Y CJS is the most commonly used method for bile duct reconstruction in the clinical setting (16,17). However, regardless of the type of CJS, because of the deprecation of the sphincter of Oddi, the problem of intestinal fluid reflux cannot be solved completely, and repeated cholangitis stimulation will cause scar tissue hyperplasia and eventually lead to anastomotic stricture, and even cancer (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven to be a safe technique by several groups and outcomes are comparable to open surgery. 1,4,8,9 Kadaba et al 10 reported a series of four hundred and sixty-two open biliary-enteric anastomoses performed for a variety of indications. They concluded that biliary reconstruction following biliary injury and an anastomosis above the confluence were the only significant independent risk factors for anastomotic leak.…”
Section: Discussionmentioning
confidence: 99%
“…These advantages of the robotic platform allow more precise dissection and suturing in narrow spaces which in theory would be especially useful for complex biliary surgery in the hepatic hilar region. 8,9,[26][27][28][29][30] In the present study, we report our initial experience with our first 27 consecutive RBS and our first 18 consecutive robotically constructed bilio-enteric anastomosis. 21 However, to date studies specifically reporting on RBS remain very limited worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…These advantages of the robotic platform allow more precise dissection and suturing in narrow spaces which in theory would be especially useful for complex biliary surgery in the hepatic hilar region. 24,25 Hence, robotic biliary surgery (RBS) has been adopted by several expert centres as an alternative MIS approach for major biliary procedures such as for hepaticojejunostomies, 8,9,23 repair of bile duct injuries 26 and resections for gallbladder cancer. 21 However, to date studies specifically reporting on RBS remain very limited worldwide.…”
Section: Introductionmentioning
confidence: 99%